New precast self-centering rocking shear wall with multiple hinged joints: Description and design approach for seismic protection of buildings. (1st July 2022) - Zhai, Zhipeng; Guo, Wei; Liu, Yanhui; Ma, Yuhong; Zhou, Fulin
Highlights: A novel precast self-centering shear wall with multiple hinged joints is proposed. The novel shear wall exhibits excellent self-centering capacity and functional recoverability. The proposed seismic design method achieves the expected performance objectives. Abstract: This paper proposes a novel precast self-centering shear wall with multiple hinged joints (PSCSWMHJ) as an alternative seismic resilient system, which is composed of pinned precast walls, pre-compressed disc spring devices (PDSD) and self-centering energy dissipation braces (SCEDB). It is featured by a dual self-centering system with the PDSD-wall component and the SCEDB resisting lateral loads. Seismic energies are expected to be mainly dissipated by S-shaped steel plate dampers installed in the SCEDB, while the precast walls are protected from damages. The damper is characterized by flexure-tension strengthening behavior that is beneficial to control structural displacement under strong earthquakes, and its seismic performance has been experimentally and numerically studied. The main objective of this study is to investigate rocking mechanism and seismic resilient design method for the PSCSWMHJ. In present study, mechanic models for the PDSD and the SCEDB are presented, and the SCEDB's hysteretic behavior is analyzed through numerical parametric studies. Rocking mechanism for the PDSDS-wall component and the PSCSWMHJ are theoretically revealed and numerically validated. Meanwhile, the influence of design parameters on their hysteretic behavior is discussed. The results show that the PSCSWMHJ has flag-shaped hysteretic curve and most of the energy is dissipated by dampers in the SCEDB. Subsequently, the step-by-step design procedure is proposed on the basis of energy balance concept for realizing seismic resilience of the PSCSWMHJ. Nonlinear dynamic analyses indicate that the design procedure is capable of achieving the expected performance objectives and the pre-selected yielding mechanism; the proposed PSCSWMHJ exhibits excellent self-centering capacity and good functional recoverability.